Adolescents' Attitudes about Teenage Marriage - Faiza Khalifatunnisa Lukmansyah; Restuning Widiasih; Deni Kurniadi Sunjaya; Binahayati Rusyidi; Laili Rahayuwati; Ermiati Ermiati (NurseLine Journal, 2024)
Adolescence is a period of crisis where if one phase in the period is not well passed, it will push adolescents into problems, one of which is teenage marriage. However, studies related to adolescents' attitudes towards marriage in adolescence for areas that are at high risk of experiencing an increase in marriage in adolescence are still limited. This research aims to obtain an overview of teenagers' attitudes in the Bangka Belitung Islands Province regarding early marriage in terms of 7 related dimensions. This research is a documentation study of secondary data from the research team "Comprehensive Study of the Stunting Reduction Acceleration Program in Bangka Belitung Islands Province," and the method used in the research is quantitative descriptive. The population of this study is adolescents aged 15-20 years in the Bangka Belitung Islands Province, which is part of the previous research data. The sampling technique used total sampling, and after screening to see the completeness of the data, there were 206 complete data. Data was collected using the EMAS (Early Marriage Attitude Scale) questionnaire. The analysis technique used is the univariate data analysis technique using a computer software program. The results show that most respondents (54.9%) have a negative attitude about teenage marriage. The conclusion of this research is that the attitudes of teenagers in the Bangka Belitung Islands Province tend to reject (negatively) teenage marriage in terms of the respondents' characteristics and each dimension of attitude research examined in this study.